1968
DOI: 10.2151/jmsj1965.46.4_308
|View full text |Cite
|
Sign up to set email alerts
|

Power Spectra of Large-Scale Disturbances over the Tropical Pacific

Abstract: The power spectra of the meridional component of the wind from the ground to the 30-km level at 17 stations in the tropical and sub-tropical Pacific are studied based on special upper wind observations taken during the period April through July 1962.In equatorial latitudes, the power spectra show a peak at a period close to 4 days corresponding to the passage of "equatorial waves" in the lower tropospheric easterlies. A very large spectral density is found at the periods 4 to 5 days throughout the upper tropos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
68
1
1

Year Published

1972
1972
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 135 publications
(83 citation statements)
references
References 21 publications
11
68
1
1
Order By: Relevance
“…We cannot say conclusively about the disturbance in 1958, but we notice for the 1956 data that this wave looks like the type of n =1, is e., the center of the wave lies on latitudes about 10°N. Yanai (1963) has reported the n =1 type disturbance propagating westward with the 6-day period at 200 mb for the 1958 data which are the same data in this study, but we cannot found this type of disturbance in this study. We consider that the disturbance reported by Yanai (1963) is the upper part of the lower tropospheric wave with the wavelength of 3,000 km mentioned above.…”
Section: Horizontal Wavelengthcontrasting
confidence: 51%
See 4 more Smart Citations
“…We cannot say conclusively about the disturbance in 1958, but we notice for the 1956 data that this wave looks like the type of n =1, is e., the center of the wave lies on latitudes about 10°N. Yanai (1963) has reported the n =1 type disturbance propagating westward with the 6-day period at 200 mb for the 1958 data which are the same data in this study, but we cannot found this type of disturbance in this study. We consider that the disturbance reported by Yanai (1963) is the upper part of the lower tropospheric wave with the wavelength of 3,000 km mentioned above.…”
Section: Horizontal Wavelengthcontrasting
confidence: 51%
“…Yanai (1963) has reported the n =1 type disturbance propagating westward with the 6-day period at 200 mb for the 1958 data which are the same data in this study, but we cannot found this type of disturbance in this study. We consider that the disturbance reported by Yanai (1963) is the upper part of the lower tropospheric wave with the wavelength of 3,000 km mentioned above.…”
Section: Horizontal Wavelengthsupporting
confidence: 49%
See 3 more Smart Citations